The Best Practice of Services for Cancer Patients: A Scoping Review - Tongtem, Ekkarat; Prakobkit, Kanittraporn; Tanadkar, Nisa; Sasat, Siriphan (Journal of The Royal Thai Army Nurses, 2023)
The objective of this study was to collect and analyse model/methods of pre-treatment, treatment, and post-treatment phases in the institutions providing best practice services both nationally and internationally. The scoping review was used as a conceptual framework and research articles were selected from seven countries. Seventy out of 2,553 research studies were met criteria. Content analysis was used based on the Donabedian model. The results were summarized in 4 phases: 1) Pre-treatment phase, focuses on the quality of the management system and screening. 2) Treatment phase, emphasizes on standard care and practice guideline. 3) Post-treatment phase, centres on using the psychosocial care service, creating a network and developing a care system and 4) Unspecified treatment phase, emphasizes on integrated care with patient-centred care using communication and virtual technology for counselling.